Faktor-Faktor yang Berhubungan dengan Kualitas Hidup Orang dengan HIV/AIDS (ODHA) di Yayasan Sehat Peduli Kasih, Kota Semarang - Ausy Hawais Monasel; Henry Setyawan Susanto; Sri Yuliawati; Dwi Sutiningsih (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: HIV/AIDS is still considered as a deadly and hard to be cured disease by the society and therefore raises negative perceptions towards People Living with HIV/AIDS (PLWHA). These negative perceptions can influence the quality of life of PLWHA, where the worse quality of life that they have, the greater chances for them to develop AIDS. This study aims to analyze the factors associated to the quality of life of PLWHA.Methods: The population of this study is PLWHA in Semarang City who are currently undergoing ART therapy and are under the assistance of Yayasan Sehat Peduli Kasih. The study was conducted on October – November 2020 towards 70 subjects whom were chosen using the purposive sampling technique. Instrument used for this study was online questionnaires. Data were analyzed with univariate and bivariate analysis using a chi-square test.Result: The results showed that 54.3% of the subjects were having poor quality of life. Factors that are associated with the quality of life of PLWHA are income level (p=0.009), duration of diagnosis (p=0.004), duration of ART therapy (p=0.002), level of family support (p=0.007), level of stigma (p<0.001) and level of depression (p<0.001). Meanwhile gender, age, marital status, education level, employment status and the level of medication adherence did not associate with the quality of life of PLWHA.Conclusion : Based on these results, it is recommended to conduct a comprehensive social activity that is focused on improving the mental health and the quality of life of PLWHA where all patients with any backgrounds could freely participate.